Active shooter response training : lone wolf to complex coordinated attacks - Hyderkhan, Scott M. (New York, NY : Routledge, 2020)
"Active Shooter Response Training, 2nd Edition, provides expanded and updated training in the skills police officers need to respond successfully to any active shooter situation. Gun violence is on the increase, from hate crimes like the murders at Mother Emmanuel or the Tree of Life Synagogue to the recent attacks in schools and on country music venues in Las Vegas and Thousand Oaks, CA. Officers must be trained to respond quickly and appropriately to the gunman and to those injured or traumatized in the attack. This field manual addresses all facets of preparation and response, from complex logistical organization to collective and individual tactics, as well as special units or special skills tasks. Based on time-tested military training doctrine, the program described here offers a template for agencies of all sizes to offer effective training that utilizes the time officers have available. Hyderkhan, now with a wide range of expert contributors, covers all aspects of the active shooter response (ASR) mission, from risk analysis to logistical planning for mass casualty events, including medical care and evacuation, reunification procedures, and post-incident investigation. Active Shooter Response Training, 2nd Edition, provides the tools needed to prevent or mitigate tragedy in our communities, including a training video and PowerPoint slides. This book is directed to law enforcement agencies, training organizations, individual trainers, police leaders,and individual officers, both international and domestic. It has some potential as recommended readying in policing courses at the community college and university level"--
OCLC-licensed vendor bibliographic record.
Keywords: Criminal snipers -- United States; Mass murder -- United States; Law enforcement -- United States -- Planning; Violence -- United States; Emergency management -- United States; LAW / Forensic Science